Bydgoszcz wpatrzona w przyszłość. Obchody jubileuszu 600-lecia miasta w 1946 roku (Kronika Bydgoska, 2014)
The 600th anniversary of chartering the city of Bydgoszcz by Casimir the Great, celebrated in 1946, became a pretext to organize jubilee festivities. In August 1945, at the meeting of the Municipal National Council, the decision was made that the event will be organized by the Committee for the celebration of the 600th anniversary of the city. Its activity was joined by representatives of the local authorities, business self-government, public institutions and social organizations. As a result of effective efforts, the patronage over the jubilee was taken by President of Poland B. Bierut and Prime Minister E. Osóbka-Morawski along with the majority of ministers from his Cabinet. In order to make activities more efficient, the Presidium of the Committee was appointed, led by Chairman J. Twardzicki and several divisions responsible for removal of war debris and cleaning of the city, preparation of solemn commemorations, cultural and sporting events, and the Pomeranian Exhibition of Industry, Crafts and Trade. Official celebrations had continued between April 19 and September 1, 1946, filled with an extensive calendar of events. The Committee focused primarily on issues related to the present and past of the city, placing emphasis on providing to Bydgoszcz the greatest prospects for development. The event achieved organizational success. Many cultural institutions operating these days in Bydgoszcz were originated in that period. The jubilee also left its mark on the spatial an architectural image of the city.